Controle de oídio em seringueira e sua interferência na população do ácaro Calacarus heveae Feres - Vieira, Marineide Rosa [UNESP]; Gomes, Eduardo Caminero; Matos, Carlos Alberto Oliveira de [UNESP] (Grupo Paulista de Fitopatologia, 2006)
A cultura da seringueira, Hevea brasiliensis (Willd. ex. Adr. de Juss.) Müell. Arg., pode ser atacada pelo fungo Oidium heveae Steinm e pelo ácaro Calacarus heveae Feres, causadores de desfolha em seringais paulistas. O presente trabalho teve por objetivo avaliar o efeito do fungicida sistêmico fenarimol no controle do fungo e a sua interferência na população de C. heveae. Comparou-se a sua aplicação em quatro momentos: 1- uma aplicação no reenfolhamento das plantas (agosto); 2- uma aplicação em janeiro; 3- duas aplicações, uma no reenfolhamento e uma em março; 4 - quatro aplicações durante o ciclo da cultura. Nas quatro situações, o fungicida reduziu os sintomas da doença, entretanto houve ressurgência dos ácaros. Considerando-se o manejo conjunto de O. heveae e C. heveae o melhor resultado foi obtido com duas aplicações do fungicida.

The rubber tree, Hevea brasiliensis (Willd. ex. Adr. de Juss.) Müell. Arg., can be attacked by the Oidium heveae Steinm fungus and the Calacarus heveae Feres mite, which cause leaf fall in areas of the São Paulo State. This study had as objective the evaluation of the effect of the systemic fungicide fenarimol, in the fungus control and its interference on C. heveae population. Four ways of application were compared: one application during the new leaves growth period (August); one application in January; two applications: one in the new leaves growth period and one in March; four applications during the cycle of the culture. The fungicide reduced the disease symptoms in all the treatments; however mite resurgence was detected. Considering the integrated management of O. heveae and C. heveae the best result was obtained by using two applications of the fungicide.
Control of Oidium on rubber tree and it's interference on the mite Calacarus heveae Feres population
Keywords: eriofídeo; sintomas; manejo; Oidium heveae; eriophyid; symptoms; management; Oidium heveae